SWOT Analysis Of Strategic Management Based On Non-Formal School In Improving The Quality Of Islamic Education - Desi Dwi Anissa; Ahmad Minanur Rohim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Al-Kamal Integrated Islamic Boarding School in Blitar plays a strategic role in integrating religious and general education to produce a competitive Muslim generation in the global era. However, challenges such as limited modern facilities and funding become obstacles in improving the quality of education. This study aims to analyze the implementation of strategic management based on non-formal schools in improving the quality of Islamic education in the Islamic boarding school. A qualitative approach with a case study method was used, involving in-depth interviews, participatory observation, and document analysis. The results of the study indicate that the Islamic boarding school has strengths in the form of a strong vision and mission, strategic location, flexible flagship programs, and adequate facilities. However, weaknesses such as dependence on student tuition fees and limited technological facilities hinder further development. Great opportunities such as government support and the increasing trend of public interest in Islamic education provide space for the Islamic boarding school to continue to develop. Threats from competition with other Islamic boarding schools and the challenges of globalization demand more significant innovation. In conclusion, the implementation of strategic management at Al-Kamal Integrated Islamic Boarding School is effective in improving the quality of education by optimizing strengths and opportunities, although improvements are needed in diversifying funding, increasing technological facilities, and adapting the curriculum based on religious and general integration. This study recommends strengthening collaboration with the government, NGOs, and the private sector to support the sustainability of education that is more inclusive and relevant to the demands of the times